2016
DOI: 10.1038/srep23264
|View full text |Cite
|
Sign up to set email alerts
|

Identification of E-cadherin signature motifs functioning as cleavage sites for Helicobacter pylori HtrA

Abstract: The cell adhesion protein and tumour suppressor E-cadherin exhibits important functions in the prevention of gastric cancer. As a class-I carcinogen, Helicobacter pylori (H. pylori) has developed a unique strategy to interfere with E-cadherin functions. In previous studies, we have demonstrated that H. pylori secretes the protease high temperature requirement A (HtrA) which cleaves off the E-cadherin ectodomain (NTF) on epithelial cells. This opens cell-to-cell junctions, allowing bacterial transmigration acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 56 publications
2
85
0
Order By: Relevance
“…Among them, E-cadherin and Smad3 were further detected in protein expression levels by Western blotting. E-cadherin is a crucial cell adhesion molecule and is considered to be a decisive inhibitor for tumor metastasis122829. Smad3 is a key molecule of the TGF-β/Smad signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, E-cadherin and Smad3 were further detected in protein expression levels by Western blotting. E-cadherin is a crucial cell adhesion molecule and is considered to be a decisive inhibitor for tumor metastasis122829. Smad3 is a key molecule of the TGF-β/Smad signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently identified the cleavage sites of H. pylori HtrA in E-cadherin. Mass-spectrometry-based proteomics and Edman degradation revealed three signature motifs containing the [VITA]-[VITA]-x-x-D-[DN] sequence pattern as preferentially cleaved by HtrA [28]. The results of our studies also suggest that the presence of calcium ions blocks HtrA-mediated cleavage by interfering with the accessibility of calcium-binding regions between the individual EC domains harboring the HtrA cleavage sites [29].…”
Section: Introductionmentioning
confidence: 91%
“…The mechanism by which C. jejuni opens tight junctions is yet unknown. For both pathogens, an HtrA-mediated transmigration process was observed [20, 21, 28], enabling bacterial contact with basolaterally expressed receptors, such as α5β1 integrins or fibronectin [53, 54], but also allowing the bacteria to directly interact with cells of the immune system. It is currently being investigated whether C. jejuni prefers the transcellular migration or paracellular route, or whether this pathogen combines two pathways to overcome the epithelial barrier [48].…”
Section: Introductionmentioning
confidence: 99%
“…The serine protease HtrA has been recently introduced as a novel secreted virulence factor, cleaving the tumor suppressor and adherens junction protein E‐cadherin. A novel study identified three signature motifs in E‐cadherin containing the [VITA]‐[VITA]‐x‐x‐D‐[DN] consensus sequence, which was preferentially cleaved by HtrA . However, research progress is mainly hampered by the lack of available htrA mutants.…”
Section: Importance Of Serine Proteasehtramentioning
confidence: 99%